Effect of chemical treatment of multi-walled carbon nanotubes on the specific capacitance of supercapacitors - Valeriy V. Golovakhin; Ekaterina Yu. Kim; Oksana N. Novgorodtseva; Alexander G. Bannov (Chimica Techno Acta)
To date, the research on carbon nanomaterials has progressed rapidly. More than 400 papers were written in 2021 on the application of carbon nanomaterials in various fields. The high demand for the use of such materials has increased due to a sharp increase in the demand for semiconductor materials and materials for supercapacitor electrodes and other electrical devices. Despite the unique physical properties of carbon nanomaterials, there are limitations to their use. To solve this problem, various methods of modifying the surface, both through chemical interactions and physical adsorption, were proposed. One of these methods is chemical modification. The evaluation of effect of chemical treatment parameters on the properties of carbon nanomaterials is an urgent task due to the fact that the chemistry of the processes is poorly understood. In this work, the effect of concentrated sulfuric and nitric acids on the change of specific surface area, elemental composition, composition of functional groups, and also on the change of specific capacitance was considered. It is believed that both the porosity and the functional groups formed during oxidation contribute to the change in specific capacitance. The specific surface area of all samples decreased on average by a factor of 1.5–3 after the chemical treatment. Different oxygen and sulfur-containing functional groups are observed after the chemical treatment. The highest specific capacitance of the treated carbon nanofibers was 114 F/g.